Folklore-based storytelling: counseling techniques to develop happiness in children - Mujiyati, Mujiyati; Sofwan, Adiputra (Indonesian Institute for Counseling, Education and Therapy (IICET), 2024)
The purpose of this study was to increase the level of children's happiness using Folklore-Based Storytelling, which develops ideogenous values in the implementation of counseling interventions. Happiness is defined as a state of joy and peace free from all problems. Storytelling is an extraordinary ability in storytelling that functions to entertain children's life values. The use of the folklore approach is based on the fact that almost all ages like stories that are told orally. The research method used is a mixed method approach with a sequential exploratory design. Qualitative design using Interpretative Phenomenological Analysis (IPA) explores how individuals understand their personal and social world through a detailed examination of their lives's experiences. The quantitative research design used is a single subject. The results of the qualitative analysis concluded that happiness according to the subject refers to the state of acceptance, attention, imagination, dreams, hopes, feelings of security, feelings of being loved, recognition, praise, appreciation, self-involvement, being heard. While the results of the feasibility test technique showed that the PND test results showed 5 points above the horizontal line PND is from 5 points of the intervention phase. This shows that the storytelling technique is very effective in developing children's happiness. Storytelling with a folklore approach is believed to be able to bring out happiness in children.